2022
DOI: 10.1161/circulationaha.122.060308
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Plaque Imaging to Accelerate Coronary Artery Disease Drug Development

Abstract: Coronary artery disease (CAD) remains the leading cause of adult mortality globally. Targeting known modifiable risk factors has had substantial benefit, but there remains a need for new approaches. Improvements in invasive and noninvasive imaging techniques have enabled an increasing recognition of distinct quantitative phenotypes of coronary atherosclerosis that are prognostically relevant. There are marked differences in plaque phenotype, from the high-risk, lipid-rich, thin-capped atheroma to the low-risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Numerous studies have evaluated the impact of statin therapy on plaque burden and plaque composition. 79 The PARADIGM registry involving 1255 patients who underwent serial CCTA, showed statin therapy to accelerate calcifications of non-calcified plaques, thus conferring plaque stabilization. 77 Progression of calcified plaque was not associated with MACE, while in contrast rapid progression of non-calcified lesions was reflective of unstable CAD and associated with future adverse outcomes.…”
Section: The Role Of Coronary Computed Tomography Angiography In Pati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have evaluated the impact of statin therapy on plaque burden and plaque composition. 79 The PARADIGM registry involving 1255 patients who underwent serial CCTA, showed statin therapy to accelerate calcifications of non-calcified plaques, thus conferring plaque stabilization. 77 Progression of calcified plaque was not associated with MACE, while in contrast rapid progression of non-calcified lesions was reflective of unstable CAD and associated with future adverse outcomes.…”
Section: The Role Of Coronary Computed Tomography Angiography In Pati...mentioning
confidence: 99%
“…Furthermore, the direct visualization of coronary atherosclerosis by CCTA allows for the evaluation CAD burden and morphology and, given its non-invasive nature, allows for serial assessment to identify temporal changes in an individual’s disease process. 79 Quantitative CCTA evaluation of atherosclerosis 135–141 —coupled with the near universal availability of CT scanners—may provide a useful tool to evaluate the effectiveness of medical therapy and lifestyle interventions over time integrating large-scale randomized controlled trial data with an ‘ n of 1’ approach that is dictated by actual CAD compared to optimization of imprecisely associated risk factors within a single individual ( Table 5 ). In the meantime, assessment of both stenosis and a visual assessment of plaque burden such as the segment involvement score, as advocated by CAD-RADS 2.0, 142 could significantly improve ASCVD risk stratification in current clinical practice.…”
Section: Future Directionsmentioning
confidence: 99%
“…The promise of more advanced imaging techniques should enable following the progression of morphological characteristics of calcification to contribute to prognostic assessment of high-risk, vulnerable patients and may be helpful in the development of novel therapies. 108 For example, fragmented calcification on histology corresponds to spotty calcification on CCTA, which links to greater risk of rupture compared with sheet calcification on histology, which corresponds to diffuse/dense calcification on radiology. 109 Microcalcification, considered a high-risk plaque feature on histology, still presents a challenge for current noninvasive imaging techniques, but advanced imaging modalities such as PCCT and DECT offer promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that improvements in CAD plaque morphology appear to be associated with reductions of MACE risk, but at present, this evidence is insufficient for application in regulatory approval. For acceptance as a surrogate measure o drug development tool, it is essential that academic clinicians engage with both the pharmaceutical industry and regulatory authorities to develop an evidence base and consensus on specific CT-based measures that most closely predict the effect of intervention on MACE ( 10 ).…”
Section: Introductionmentioning
confidence: 99%